2019
DOI: 10.1002/cssc.201901198
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Hydrogenation of Ethyl Levulinate to 1,4‐Pentanediol over 2.8Cu‐3.5Fe/SBA‐15 Catalyst at Low Loading: The Effect of Fe Doping

Abstract: Bimetallic Cu–Fe catalysts with low loading were prepared for hydrogenation of ethyl levulinate (EL) to 1,4‐pentanediol (1,4‐PDO). Among them, 2.8Cu‐3.5Fe/SBA‐15 (Cu/Fe molar ratio of 1:1.5) performed best, capable of converting EL to the key intermediate γ‐valerolactone (GVL) at 140 °C with 97 % yield. It can also be used to hydrogenate GVL to 1,4‐PDO with 92.6 % selectivity or convert EL to 1,4‐PDO in one pot. The high activity of the catalyst at such a low loading was attributed to the highly dispersed meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 48 publications
0
19
0
Order By: Relevance
“…According to the performance of the traditional CuCr catalyst [6] as well as our previous work [26], Cu could be suitable for catalyzing the furfural hydrogenation step. Meanwhile, based on our previous work [27,28], SBA-15, which has a tunable mesoporous framework structure and can be functionalized by sulfonic acid, could be an appropriate acidic support for xylose dehydration. Therefore, in this work, sulfonic acid functionalized SBA-15-supported Cu catalyst was employed for the one-pot conversion of xylose to furfuryl alcohol.…”
Section: Introductionmentioning
confidence: 99%
“…According to the performance of the traditional CuCr catalyst [6] as well as our previous work [26], Cu could be suitable for catalyzing the furfural hydrogenation step. Meanwhile, based on our previous work [27,28], SBA-15, which has a tunable mesoporous framework structure and can be functionalized by sulfonic acid, could be an appropriate acidic support for xylose dehydration. Therefore, in this work, sulfonic acid functionalized SBA-15-supported Cu catalyst was employed for the one-pot conversion of xylose to furfuryl alcohol.…”
Section: Introductionmentioning
confidence: 99%
“…Another potential electrochemical route for the production of a diol intermediate from this feedstock is the reduction of levulinate bio-esters. First, the esterification of LA or furfuryl alcohol with bio-alcohols produces levulinate esters, which can then be reduced to 1,4-pentanediol, a building block for the production of high-strength biodegradable polyester polyols, polyurethanes, and other polymeric materials, as well as important fine chemical intermediates. The conventional thermochemical production of this diol involves the use of noble metal catalysts (such as Rh and Ru) and/or high temperatures (>150 °C) and pressures of H 2 gas (>6 MPa) . In contrast, the respective electrochemical route may be performed at ambient conditions.…”
Section: Critical Discussionmentioning
confidence: 99%
“…Although the signal intensity of (100) plane for these catalysts slightly decreased, the (110), ( 200) and ( 210) diffraction peaks were maintained, which revealed that the mesoporous structure of SBA-15 was preserved after metal loading. In addition, the SAXRD peaks of PtNi/SBA- 15 shifted to a higher 2θ region, corresponding to a smaller d-spacing, which was attributed to the fact that a large number of nanoparticles loaded into the mesoporous pores leading to the structural shrinkage of the mesoporous silica framework (Goyal et al, 2016;Deng et al, 2019 The TEM images were presented in Figure 4 and Supplementary Figures S1, S2. The average diameter of the metal particles on the catalysts was listed in Table 1.…”
Section: Structural Characterization Of the Catalystsmentioning
confidence: 99%
“…Given this background, we design a SBA-15 (Santa Barbara Amorphous-15, a stable mesoporous silica molecular sieve, which was developed by researchers at the University of California at Santa Barbara) supported PtNi nanoalloys catalyst for the C=O hydrogenation of FF/HMF in water under mild conditions, since SBA-15 with advantageous feature (e.g., high heat resistance, variable framework compositions, and low diffusion barrier for the reactants) has been reported to efficiently adsorb carbonyl groups, which could further promote the selective carbonyl hydrogenation ( Zhao et al, 1998 ; Huang et al, 2014 ; Deng et al, 2019 ; Samikannu et al, 2020 ). The catalyst was synthesized by a two-step method without the use of gaseous hydrogen or NaBH 4 as reductant ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%